Determinants of long act reversible contraceptive utilization among HIV positive reproductive age women attending ART clinic in South West Ethiopia - Bilisumamulifna Tefera Kefeni; Sitota Tesfaye; Kenbon Bayisa; Ebissa Negara; Feyiso Bati (Contraception and Reproductive Medicine, 2023)
Abstract Background Identifying the determinants of long-acting contraceptive utilization and managing the sexual and reproductive health of HIV-infected women is critical to reducing HIV transmission and maternal mortality. However, the determinants of long-acting contraceptive utilization have not been well understood in resource-limited settings like Ethiopia. The aim of this study was to identify determinants of long-acting reversible contraceptive utilization among HIV-positive women on ART in southwest Ethiopia. Methods A facility-based, unmatched case control study was conducted from July 24 to August 28, 2021, in south-west Ethiopia. The study participants were HIV positive women, with a sample size of 109 cases and controls. An interviewer administered a questionnaire, and a check list was used for data collection. A systemic random sampling technique was used to collect data from cases and controls. Bivariate and multivariable logistic regressions were employed to determine the determinants of LARC utilization among HIV-positive women. To demonstrate the strength of the determinant, the odds ratio was calculated with 95% confidence intervals, and a P-value less than 0.05 was used to declare statistical significance. Result A total of 324 women (108 cases and 216 controls) of reproductive age who were HIV positive were interviewed, with a response rate of 99.0%. urban residence (AOR = 2.67, 95%CI: 1.23- 5.77), having formal education (AOR = 2.93, 95% CI:1.36, 6.34), being counseled by health care provider (AOR = 5.42,95% CI: 2.67–11.03), no future fertility intention (AOR = 2.87, 95% CI:1.44–5.70), having CD4 count less than 500 cell/mm3 (AOR = 4.18,95% CI:2.12–8.23), having information of HIV transmission from mother to child (AOR = 3.65,95% CI:1.49–8.95),not using condom during sexual intercourse (AOR = 4.86,95% CI:2.46–9.62),,having knowledge towards LARC (AOR = 2.38,95% CI:1.24–4.58) and attitude towards LARC (AOR = 6.41,95%CI:3.16–13.0) were independent determinants of LARC utilization among HIV positive women. Conclusion and recommendation Women being counseled by a health care provider, having no future fertility intention, and having a CD4 count less than 500 cells/mm3 were found to be determinants of long-acting contraceptive method utilization among HIV-positive reproductive-age women. Also, our study supports the WHO Strategic Concepts for Improving the Links between Family Planning and HIV/AIDS Policy, Programs, and Services. It is recommended that Health care providers should use these factors as base line during family planning counseling and service delivery.